2021
DOI: 10.1177/03635465211034511
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Course of Recovery After Hip Arthroscopy for Femoroacetabular Impingement According to the International Hip Outcome Tool–12 and Hip Outcome Score Sports Subscale

Abstract: Background: A paucity of literature exists regarding trajectories of functional and sports-specific recovery after hip arthroscopy for femoroacetabular impingement syndrome (FAIS). Purpose: To determine if subgroups of patients exist based on the recovery trajectory of patient-reported outcomes (PROs) after hip arthroscopy for FAIS in the short-term period and to determine clinical predictors for these subgroups of patients. Study Design: Case-control study; Level of evidence, 3. Methods: A prospectively maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…Thus far, PROs have been widely used to characterize recovery and have served as a primary assessment of improvement after hip arthroscopy. 42 In the current study, there were universal improvements in the PROs at 6 months, and the proportion of patients meeting the PROs at 6 months was greater than at 3 months. The overall proportion achieving thresholds for MCID and especially PASS was relatively low but at 6 months, which is not unexpected given that we used 1-year postoperative benchmarks.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Thus far, PROs have been widely used to characterize recovery and have served as a primary assessment of improvement after hip arthroscopy. 42 In the current study, there were universal improvements in the PROs at 6 months, and the proportion of patients meeting the PROs at 6 months was greater than at 3 months. The overall proportion achieving thresholds for MCID and especially PASS was relatively low but at 6 months, which is not unexpected given that we used 1-year postoperative benchmarks.…”
Section: Discussionsupporting
confidence: 42%
“…Furthermore, while each patient was prescribed a rehabilitation process standard to this institution, the therapist, rehabilitation facility, and timing of when patients may have progressed through each phase of rehabilitation were heterogeneous between patients. Lastly, this study only analyzed gait, and other mechanical tasks such as squatting 44 , 45 or additional demographic or disease-related factors 42 , 46 may be more representative of functional improvement after hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The 74 included studies consisted of 17 case series, § 6 case-control studies, 3 , 7 , 19 , 37 , 51 32 cohort studies, ‖ and 19 cross-sectional studies. ¶ A summary of the characteristics of each study is given in Appendix Table A2 .…”
Section: Resultsmentioning
confidence: 99%
“…As inherent to the treatment of FAI syndrome, patients underwent a trial of nonoperative measures before undergoing surgery if indicated, which was the same time when enrollment and kinematic testing were performed. Patients diagnosed with FAI syndrome were excluded for any of the following reasons: radiographic evidence of osteoarthritis (To ¨nnis grade .1); history of chronic low back pain or reports of low back pain within the 6 months before study enrollment 5,30 ; history of surgery to the indexed or contralateral hip; history of any systemic disorders (musculoskeletal, neurologic, cardiorespiratory, integumentary, or endocrine system) that would prevent participation in the study tasks; and history of a developmental hip disorder, such as Legg-Calve ´-Perthes disease, slipped capital femoral epiphysis, or developmental hip dysplasia. All patients with FAI syndrome who met the study inclusion criteria for the current study were prospectively recruited for participation from December 2018 to December 2019.…”
Section: Fai Syndrome and Hip Arthroscopy: Patient Selectionmentioning
confidence: 99%